Perancangan Media Promosi Wisata Kayangan Api Berbasis Videografi Sebagai Upaya Pengenalan Pariwisata Kabupaten Bojonegoro - Firdaus, Muhammad Yusuf; Martono, Siswo; Yurisma, Dhika Yuan (Jurnal Art Nouveau, 2017)
Bojonegoro Regency is one of regencies in East Java province which is geographically quite unique, which in addition has a lot of forest, most of Bojonegoro also has mountains, valleys and plains as well as the persistence of the forest area or inland. This diversity raises exotic nature so that it can be used as a tourist attraction. Therefore, as the introduction of Bojonegoro in East Java tourism as well as to promote the tourism sector in Bojonegoro, the authors put it in the form of the design of nature-based tourism promotion videography. This study uses qualitative methods with data collection technique using observation, interviews, literature, existing studies, and study competitors. The concept used in the design is